Le processus de référence dans un service universitaire de psychologie le niveau de satisfaction du consummateur - Sabourin, Stéphanie; Gendreau, Pierre; Labrecque, Michelle (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of this study was to examine the satisfaction level of referred patients in a university mental health centre. The compliance rate with referral was also studied. The sample consisted of 48 referred cases and a comparison group of 15 clients who remained in treatment for 20 sessions. The results went in the predicted direction. Referred cases were significantly less satisfied than clients who were treated at our clinic. Moreover, there was a sharp contrast between the preciseness of proposed referrals and the low compliance rate observed. These findings were discussed along with methodological issues raised by this study.